2016
DOI: 10.1120/jacmp.v17i1.5682
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effects of positioning shifts using 6D‐frameless stereotactic Brainlab system in hypofractionated intracranial radiotherapy

Abstract: Dosimetric consequences of positional shifts were studied using frameless Brainlab ExacTrac X‐ray system for hypofractionated (3 or 5 fractions) intracranial stereotactic radiotherapy (SRT). SRT treatments of 17 patients with metastatic intracranial tumors using the stereotactic system were retrospectively investigated. The treatments were simulated in a treatment planning system by modifying planning parameters with a matrix conversion technique based on positional shifts for initial infrared (IR)‐based setup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
(43 reference statements)
0
10
0
1
Order By: Relevance
“…If rotational setup errors are detected and corrected for, this margin can be reduced to 0.1 mm/cm . Another study suggested that target coverage is assured if a margin of 2 mm is applied . Regarding intrafractional motion, a 1‐mm margin was proposed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If rotational setup errors are detected and corrected for, this margin can be reduced to 0.1 mm/cm . Another study suggested that target coverage is assured if a margin of 2 mm is applied . Regarding intrafractional motion, a 1‐mm margin was proposed .…”
Section: Discussionmentioning
confidence: 99%
“…30 Another study suggested that target coverage is assured if a margin of 2 mm is applied. 47 Regarding intrafractional motion, a 1-mm margin was proposed. 31 However, none of these recommendations take into account OAR-sparing.…”
Section: Discussionmentioning
confidence: 99%
“…It may pose unexpected deviations on the result since the algorithm has a fixed detection margin and assumes no setup uncertainty. According to Jin et al, 25 mean translational and rotational corrections were 2.45 mm and 1.84° in the 6D frameless BrainLAB system using x‐ray correction. If the average radius from the isocenter to the end of a setup device is presumed to be 15 cm, the resultant couch motion with 1.84° will be 4.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, high localization accuracy (typically within 1 mm) is needed in intracranial stereotactic radiotherapy (SRT) in order to not compromise the local control and to minimize the risk of intracranial complications . Several research groups reported that IGRT techniques including orthogonal kV‐imaging, oblique kV‐imaging, kV‐cone‐beam computed tomography (CBCT), and megavoltage (MV)‐CT have high accuracy for positioning verification in intracranial SRT. However, a clinical problem is presented by intracranial SRT plans that consist of a number of noncoplanar beams that cannot be achieved with the use of the above‐cited techniques.…”
Section: Introductionmentioning
confidence: 99%